Gestión administrativa de la Dirección de Desarrollo Social del Gobierno Autónomo Descentralizado de la Provincia de los Ríos - Aguirre Coello, Daniela Katiuska (2018)
Social Development Directorate attached to the Provincial Government of Los Ríos-GADPLR is an organization focused on promoting, promoting and executing projects aimed at improving the quality of life of the Riosense population. Created with the purpose of providing preferential support for the promotion and protection of children, adolescents, single mothers, seniors and people with disabilities different from scarce economic resources, especially from rural and marginal urban populations of the province